Sociomedical factors affecting the birth rate in the Russian Federation - Ovod, Alla Ivanovna; Komissinskaya, Irina Gennadievna; Khorlyakov, Kirill Vladimirovich (Revista de la Universidad del Zulia, 2020)
The article considers the number of women giving birth in Russia in the context of the existing demographic problems caused by the depopulation of the country. The study evaluates the social, economic and medical factors influencing the dynamics of the number of women giving birth in the Russian Federation based on correlation and regression analysis, and also provides a short-term forecast for their further change. The implementation of the increase in the number of women giving birth in Russia is one of the current important sociodemographic tasks for the State; This will improve the demographic situation and will lay the foundations for the formation of a sufficient human resource, which will later form the country's high human capital. According to the results of forecasting the dynamics of the number of women in the work in the short term, it was determined that the downward trend in the number of women in the work will continue, since the negative impact of medical factors will remain unchanged. changes, while economic and social factors will not change.